IoT Semantic Interoperability: A Systematic Mapping Study - Venceslau, Amanda (2019)
The Internet of Things (IoT) is a paradigm in which the Internet connects people and the environment using devices and services that are spread in the user daily routine. In this scenario, different agents, devices and services are able to exchange data and knowledge using a common vocabulary or mappings that represent and integrate heterogeneous sources. This semantic interoperability is facilitated by the Semantic Web that provides consolidated technologies, languages and standards, offering data and platforms interoperability. In this context, this work reviews and analyzes the state-of-the-art of IoT semantic interoperability, investigating and presenting not only which Semantic Web technologies are employed but also the challenges that support the studies in this area of research.